Zora Neale Hurston’s Controversial Relation to the Harlem Renaissance - ALALI, SALAM (International Journal of Language and Literary Studies, 2022)
This study is about the African American Harlem Renaissance star Zora Neale Hurston and her link to this movement. She was perceived negatively by some central male figures in this movement because she didn’t follow the trend of “propaganda” for “race lifting.” She was accused of presenting a very negative image of African Americans. This image matches the stereotypical white views of the black. They believed such an image must be suppressed or marginalized in favour of something more urgent that serves the black as a whole. Others found in this approach an attempt on Hurston's part to reach and make her voice heard for the white and her interests with white publishers. In fact, she was a folklorist and anthropologist dedicated to preserving the African American heritage. She transcended the “race people” for an objective and scientific representation of her people. She examines the relationship between Hurston’s text and culture as a text, her role as outsider/ insider in telling the black folktales, occupying an anthropologist job that is classified as exclusively masculine and done by the white.